Switzerland : Staff Report for the 1999 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
For the past quarter century, Switzerland's real per capita growth rate has been substantially slower than in most other industrial countries. Unemployment has declined rapidly to 2.4 percent of the labor force in November 1999 from its 1997 peak of more than 5 percent. Inflation has edged up from exceptionally low levels. Switzerland's longstanding current account surplus was above 9 percent of gross domestic product in 1998 and is estimated to have risen further in 1999. The franc has shadowed the euro closely since January 1999, fluctuating narrowly around 1.6 Sw F/euro.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet